122 Real world outcomes of sglt2 inhibition in a hfref population. (6th June 2022) - Savage, Patrick; McElhatton, Daniel; Campbell, Michael; Bamford, Jordan; Reid, Rebecca; Dixon, Lana
Abstract : Background: Recent landmark trials such as DAPA-HF and EMPEROR-Reduced have led to the approval and implementation of Sodium/glucose cotransporter 2 (SGLT2) inhibitors as a first line therapy for heart failure with reduced ejection fraction (HFreF). However, there is a paucity of data looking at real world outcomes in heart failure patients.AimWe sought to evaluate the real-world outcomes of SGLT2 inhibition in our local HFreF population. MethodWe performed a retrospective data analysis of patients with HFrEF commenced on a SGLT2 inhibitor since September 2021. The primary composite endpoint of heart failure hospitalisations and cardiovascular (CV) death was assessed six months from initiation with historical matched controls as comparators. Secondary endpoints included change in New York Heart Association (NYHA) score and change in serum creatinine at six months. Data were extracted from local healthcare records. Data expressed as mean+/-standard deviation with p<0.05 defined as significant. Variance between groups analysed using students t test. Statistical analysis performed with SPSSTM. Results112 patients were commenced on SGLT2 inhibition (dapagliflozin n=99, 97%, empagliflozin n=3, 3%). The mean age was 66.6+/-14.6 years (59%, male n=66) with a mean LVEF at baseline of 28.4+/-14.7%. The predominant aetiology of heart failure was ischaemic (n=71, 64%) with 17% of patients being diabetic (n=19). In patients with HFreF commenced on SGLT2 inhibition, at six months, there was a significant reduction in the primary composite endpoint compared to controls (p=0.04) (Figure 1). There was a significant difference in CV mortality compared to controls (2 vs 11, p<0.01) with a lower number of heart failure hospitalisations in the SGTL2 groups (34 vs 43); however, this did not reach statistical significance (p=0.06). There was a significant reduction in mean NYHA score following initiation of an SGLT2 inhibitor (2.15+/-0.89, n=112 to 1.93+/-0.77, n=109; p<0.01). Renal parameters including serum creatinine initiation (105.5+/-31umol/L vs 90+/-38umol/L, p=ns) and potassium (4.5+/-0.48 mmol/L vs 4.7+/-0.61 mmol/L, p=ns) remained stable at six months. Conclusion: In a real-world population of HFreF patients, SGTL2 inhibitors produce a statistically significant reduction in heart failure hospitalisations and CV death with a significant reduction in QOL outcomes measured by NYHA score. Furthermore, parameters of renal function remained stable following initiation of SGLT2 inhibition. Conflict of Interest: none